One C-to-U RNA Editing Site and Two Independently Evolved Editing Factors: Testing Reciprocal Complementation with DYW-Type PPR Proteins from the Moss Physcomitrium (Physcomitrella) patens and the Flowering Plants Macadamia integrifolia and Arabidopsis. Issue 9 (2nd July 2020) - Oldenkott, Bastian; Burger, Matthias; Hein, Anke-Christiane; Jörg, Anja; Senkler, Jennifer; Braun, Hans-Peter; Knoop, Volker; Takenaka, Mizuki; Schallenberg-Rüdinger, Mareike
Abstract : DYW-type PPR proteins independently evolved in mosses and flowering plants restore RNA editing defects across wide phylogenetic distances. Abstract: Cytidine-to-uridine RNA editing is a posttranscriptional process in plant organelles, mediated by specific pentatricopeptide repeat (PPR) proteins. In angiosperms, hundreds of sites undergo RNA editing. By contrast, only 13 sites are edited in the moss Physcomitrium ( Physcomitrella ) patens . Some are conserved between the two species, like the mitochondrial editing site nad5eU598RC. The PPR proteins assigned to this editing site are known in both species: the DYW-type PPR protein PPR79 in P. patens and the E+-type PPR protein CWM1 in Arabidopsis ( Arabidopsis thaliana ). CWM1 also edits sites ccmCeU463RC, ccmBeU428SL, and nad5eU609VV. Here, we reciprocally expressed the P. patens and Arabidopsis editing factors in the respective other genetic environment. Surprisingly, the P. patens editing factor edited all target sites when expressed in the Arabidopsis cwm1 mutant background, even when carboxy-terminally truncated. Conversely, neither Arabidopsis CWM1 nor CWM1-PPR79 chimeras restored editing in P. patens ppr79 knockout plants. A CWM1-like PPR protein from the early diverging angiosperm macadamia ( Macadamia integrifolia ) features a complete DYW domain and fully rescued editing of nad5eU598RC when expressed in P. patens. We conclude that (1) the independently evolved P. patens editing factor PPR79 faithfully operates in the more complex Arabidopsis editing system, (2) truncated PPR79 recruits catalytic DYW domains in trans when expressed in Arabidopsis, and (3) the macadamia CWM1-like protein retains the capacity to work in the less complex P. patens editing environment.